Physical and Sexual Violence Affecting Female Sex Workers in Abidjan, Côte d'Ivoire: Prevalence, and the Relationship with the Work Environment, HIV, and Access to Health Services. (1st May 2017) - Lyons, Carrie E.; Grosso, Ashley; Drame, Fatou M.; Ketende, Sosthenes; Diouf, Daouda; Ba, Ibrahima; Shannon, Kate; Ezouatchi, Rebecca; Bamba, Amara; Kouame, Abo; Baral, Stefan
Abstract : Background: Violence is a human rights violation, and an important measure in understanding HIV among female sex workers (FSW). However, limited data exist regarding correlates of violence among FSW in Côte d'Ivoire. Characterizing prevalence and determinants of violence and the relationship with structural risks for HIV can inform development and implementation of comprehensive HIV prevention and treatment programs. Methods: FSW > 18 years were recruited through respondent driven sampling (RDS) in Abidjan, Côte d'Ivoire. In total, 466 participants completed a socio-behavioral questionnaire and HIV testing. Prevalence estimates of violence were calculated using crude and RDS-adjusted estimates. Relationships between structural risk factors and violence were analyzed using χ 2 tests and multivariable logistic regression. Results: The prevalence of physical violence was 53.6% (250/466), and sexual violence was 43.2% (201/465) among FSW in this study. Police refusal of protection was associated with physical (adjusted Odds Ratio [aOR]: 2.8; 95% confidence interval [CI]: 1.7 to 4.4) and sexual violence (aOR: 3.0; 95% CI: 1.9 to 4.8). Blackmail was associated with physical (aOR: 2.5; 95% CI: 1.5 to 4.2) and sexual violence (aOR: 2.4; 95% CI: 1.5 to 4.0). Physical violence was associated with fear (aOR: 2.2; 95% CI: 1.3 to 3.1) and avoidance of seeking health services (aOR: 2.3; 95% CI: 1.5 to 3.8). Conclusions: Violence is prevalent among FSW in Abidjan and associated with features of the work environment and access to care. These relationships highlight layers of rights violations affecting FSW, underscoring the need for structural interventions and policy reforms to improve work environments, and to address police harassment, stigma, and rights violations to reduce violence and improve access to HIV interventions.